Enhancing Soil Health to Mitigate Soil Degradation - Douglas L. Karlen (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Five of the top ten problems facing humanity (http://cnst.rice.edu/content.aspx?id=246) over the next 50 years (food, water, energy, environment and poverty) are directly related to the health of soil resources. Several different factors, including: (a) excessive tillage; (b) inappropriate crop rotations; (c) excessive grazing or crop residue removal; (d) deforestation; (e) mining and/or fracking; and (f) construction or urban sprawl, have contributed to the global problem of soil degradation. Understanding and implementing sustainable agricultural and land management practices that improve soil health is essential for mitigating and reversing these trends, if we are to successfully meet the needs of more than 9.5 billion people who will be sharing our fragile planet by the middle of the 21st century. The overall focus for this Special Issue was on agricultural factors contributing to soil degradation and suggested strategies for mitigating and reversing those trends. The discussion was anchored by invited contributions reflecting perspectives from Africa, Australia, China, Eastern Europe, India, Latin America, North America, Russia, and Western Europe. Voluntary contributions were evaluated, and incorporated into the issue to provide a global perspective on soil degradation and strategies to mitigate its devastating effects. This Special Issue draws upon published literature addressing soil quality and/or soil health, soil and crop management strategies to mitigate soil degradation, and future research needs and strategies that will steadily improve the fragile layer that lies between us and starvation. Your participation and contributions to this important endeavor were most welcome.